2011
DOI: 10.4236/ce.2011.23036
|View full text |Cite
|
Sign up to set email alerts
|

Representation Registers in the Solution of Calculus Problems

Abstract: This article is derived from the research project registered under number 20110343 (Ruiz, 2011), and developed in Escuela Superior de Cómputo del Instituto Politécnico Nacional (IPN) (School of Computer Sciences of the National Poly-technical Institute of Mexico). The article reports on the problems found among Engineering students with respect to their resistance to using different representation registers when solving optimization problems in the Calculus Learning Unit. Use of such registers could help the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…This study also supports the conclusion reached by other scholars (e.g., see Brijlall & Ndlovu, 2013;Ledesma, 2011) that the source of difficulties with optimization problems might not necessarily be rooted in the mathematization of the processes but in the difficulty of understanding the underlying mathematical principle. The ultimate extension of this study would be to investigate whether the lab experience helped students with formulating the solution processes to solve textbook problems on optimization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study also supports the conclusion reached by other scholars (e.g., see Brijlall & Ndlovu, 2013;Ledesma, 2011) that the source of difficulties with optimization problems might not necessarily be rooted in the mathematization of the processes but in the difficulty of understanding the underlying mathematical principle. The ultimate extension of this study would be to investigate whether the lab experience helped students with formulating the solution processes to solve textbook problems on optimization.…”
Section: Discussionsupporting
confidence: 90%
“…They further suggested that "teachers needed to be aware of learners learning conflicts so as to reinforce the new concepts they encounter" (p. 17). Ledesma (2011) investigated how to identify a solid with a maximum volume built by cutting squares of various side lengths from a cardboard and folding the shape. She concluded that calculus students faced difficulties understanding the optimization process, which she considered a main obstacle in solving these problems.…”
Section: Prior Research Findingsmentioning
confidence: 99%
“…15. The belief sphere (circle 1) includes the belief itself (2), its truth value (3), the illness (4), and its truth value (5). Note that the belief (1) is in John Doe, and it includes two sub-spheres: itself (2) and its content illness (4).…”
Section: Beliefsmentioning
confidence: 99%
“…In this paper, the term representation refers to "appearances" (public representation [4]), such as expressions in natural language, algebraic formulae, graphs, or geometric figures [5]. The focus is on a diagrammatic representation that depicts things (will be defined later) that "may exist in a possible or fictional world" [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation